Incidence and predictors of mortality among neonates with congenital heart disease in Ethiopia: a retrospective cohort study - Abatwoy Ayfokru; Sisay Shewasinad; Fuad Ahmed; Mitku Tefera; Genet Nigussie; Emawaysh Getaneh; Leweyehu Alemaw Mengstie; Wegayehu Zeneb Teklehaimanot; Worku Abemie Seyoum; Mohammed Tessema Gebeyehu; Metages Alemnew; Bekahegn Girma (BMC, 2024)
Abstract Background Neonatal mortality poses a significant public health challenge in sub-Saharan Africa, with congenital heart disease emerging as the leading cause of morbidity and mortality among neonates, especially in countries like Ethiopia. Despite efforts to reduce neonatal mortality rates, Ethiopia continues to experience an increased mortality rate, particularly among neonates with congenital heart disease. This study aims to investigate the incidence and predictors of mortality in this vulnerable population within Ethiopia. Method A retrospective cohort study was conducted at an institution, involving 583 randomly selected neonates diagnosed with congenital heart disease. In the current study, the dependent variable was survival status. Data entry utilized EpiData data version 4.6, and analysis was performed using STATA version 16. Probability of death was compared using the log-rank test and Kaplan-Meier failure curve. Significant predictors were identified using bivariable and multivariate Cox regression. Model fitness and proportional hazard assumptions were evaluated using the Cox-Snell graph and Global test, respectively. Associations were assessed by adjusted hazard ratios with 95% confidence intervals. Results The study participants were followed for 4844 days. The mortality rate was 9.9%. The incidence density was 11.9 per 1000 person-days of observation. Neonatal sepsis (AHR: 2.24; 95% CI [1.18-4.23]), cyanotic congenital heart disease (AHR: 3.49; 95% CI [1.93-6.28]), home delivery (AHR: 1.9; 95% CI [1.06-3.6]), maternal history of gestational diabetes mellitus (AHR: 1.94; 95% CI [1.04-3.61]), and having additional congenital malformations (AHR: 2.49; 95% CI [1.33-4.67]) were significant predictors for neonatal mortality. Conclusion and recommendation The incidence density of mortality was high compared to studies conducted in developed countries. Neonatal sepsis, type of congenital heart disease, place of delivery, maternal history of gestational diabetes mellitus, and having an additional congenital malformation were significant predictors of mortality among neonates with congenital heart disease. Therefore, healthcare providers should pay special attention to patients with identified predictors. Furthermore, the Federal Ministry of Health, stakeholders, and policymakers should collaborate to address this issue.